Pemetaan Kemampuan Siswa pada Hasil Belajar Ujian Akhir Semester: Studi Mata Pelajaran Kimia - Marlina, Marlina (Varied Knowledge Journal, 2024)
This study aims to describe the ability of high school students in mapping summative tests in chemistry learning and identifying chemistry summative test questions. The research method used is a descriptive method with a quantitative approach. The sampling technique used was random sampling technique. The research subjects were 105 high school students. Based on the results of research and discussion, the ability of high school students shows an average in the very high category with a percentage of 19% with a frequency of 20 students. The ability of students in the high category has a percentage of 25% with a frequency of 27 students. The ability of students in the medium category has a percentage of 55% with a frequency of 58 students. The average in the low category has a percentage of 0% with a frequency of 0 students. Furthermore, the ability of students in the very low category has a percentage of 0% with a frequency of 0 students. Overall, the ability of summative test students in high schools in Tegal City is in the moderate category for learning outcomes. The implication of the research results shows that the ability of students is still in the moderate category and measures the ability of students in one semester learning.